NETRALITAS TNI DAN POLRI DALAM PENYELENGGARAAN PEMILIHAN UMUM GUNA MEWUJUDKAN KONSOLIDASI DEMOKRASI DI INDONESIA - Hakim, Yusup Rahman (Bawaslu Provinsi Jawa Barat, 2023)
This article discusses the crucial role of the neutrality of the TNI and Polri in holding general elections with the aim of realizing the consolidation of democracy in Indonesia. This research details the impact and contribution of the TNI and Polri in maintaining the integrity and security of the democratic process. By utilizing the theory of democratic consolidation, this article identifies crucial conditions, such as competitive elections, recognition of human rights, civilian control of the military, a strong party system, and the role of a consensus political elite. This writing uses qualitative research methods. This writing is supported by empirical data and in-depth analysis of violations of the neutrality of ASN including the TNI and Polri and their impact on democratic consolidation. The results of this article show that the neutrality of the TNI and Polri is not only a security guard element, but also plays an important role in supporting Indonesia's democratic foundations. Conclusions and suggestions are provided to strengthen this neutrality, including strengthening training, transparency, and community involvement as an integral part of the democratic process.